Role Of Technological Deployment And Management Style As Mediators Between Business Strategy And Performance - Tun Abdullah, Mohammad Zolkamain (2002)
The purpose of this study is to investigate the predominant business strategies adopted by organizations in the Multimedia Super Corridor (MSC); this study also examine the various types of technological deployment and management style that affect the organizations in MSC, Malaysia. Technological deployment in this study is defined to include information system (IS) architecture, strategic impact, and technological source-scanning. A typological approach is used in this study, by using Miles and Snow's typology that characterize business strategy in four categories; prospector, analyzer, defender, and reactor.